Das reminiscências trovadorescas na poesia de Álvares de Azevedo: um estudo do aspecto amoroso na Lira dos Vinte Anos - SILVA, Tallyson Tamberg Cavalcante Oliveira da (2021)
The present investigation, from a comparative perspective, analyzes the troubadour reminiscences present in the lyrical-loving poems of Lira dos Vinte Anos, a poetic work belonging to Álvares de Azevedo and which was published posthumously, in 1853. Furthermore, we show how Romanticism retakes themes and procedures typical of medieval literature, especially with regard to the lyrical-loving troubadour posture. The methodology that serves as the basis for this work is that of Residuality, proposed by Roberto Pontes, critic, essayist and retired professor of undergraduate and graduate studies in Letters at the Universidade Federal do Ceará (UFC). In the research, studies inherent to the History of Mentalities, Comparative Cultural Studies and the investigation of topoi (Toposforchung) proposed, respectively, by École des Annales, Raymond Williams and Ernst Robert Curtius, are also present. Finally, this investigation is relevant to the academic community because it addresses, in a typically romantic work, the Lira dos Vinte Anos, the medievalist aspect, still little analyzed by researchers who focus on this canonical work of our Romanticism.